2002
DOI: 10.1007/s11746-002-0496-4
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal crystallization kinetics of refined palm oil

Abstract: The induction times for the crystallization, under isothermal conditions, of refined, bleached, and deodorized palm oil from the melt were studied by viscometry. At temperatures below 295 K, the crystallization of palm oil was observed to occur in a two-stage process. This two-stage process was caused by the fractionation of palm oil, most probably into the stearin and olein fractions. At temperatures higher than 295 K, only a single-stage crystallization process was observed. As seen under polarized light mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
48
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 12 publications
9
48
0
2
Order By: Relevance
“…A similar discontinuity with temperature to that seen by Chen et al [10] is observed. They suggested that the discontinuity observed in the induction data was caused by a change in the polymorphic forms present and that below temperatures of 298 K two palm oil polymorphs, α and β' crystallised separately.…”
Section: Nucleation Datasupporting
confidence: 87%
See 3 more Smart Citations
“…A similar discontinuity with temperature to that seen by Chen et al [10] is observed. They suggested that the discontinuity observed in the induction data was caused by a change in the polymorphic forms present and that below temperatures of 298 K two palm oil polymorphs, α and β' crystallised separately.…”
Section: Nucleation Datasupporting
confidence: 87%
“…The spherulitic/needle morphologies were also observed by Kawamura [2] at 30 °C (who tentatively ascribed them to the β polymorph) and Chen et al [10] at 28 °C. Chen et al, however, identified such crystals as belonging to the β' polymorph using XRD.…”
Section: Crystal Morphology and Polymorphismsupporting
confidence: 57%
See 2 more Smart Citations
“…An increase in µ does not suddently occur after T Cr isothermal achieved, as indicated by the SFC baseline plot which is still flat until a certain period of time. If at any point SFC drastically changes from the baseline, according to Chen et al (2002), the point reflected the occurance of crystallization induction time, and improvement degree of SFC after that point illustrates the amount of µ. At low v c , µ has a high value.…”
Section: Resultsmentioning
confidence: 99%